2006
DOI: 10.1111/j.1365-2400.2006.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Density and temperature dependence of gill net catch per unit effort for perch, Perca fluviatilis, and roach, Rutilus rutilus

Abstract: The densities of perch, Perca fluviatilis L., and roach, Rutilus rutilus (L.), were estimated in six and three lakes, respectively, using mark-recapture and ranged from 25-1064 perch ha )1 and 865-2749 roach ha )1 . Effects of fish density, net type and water temperature on catch-per-unit-effort (CPUE) were analysed by generalised linear models (GLM) and generalised additive models (GAM). GAMs were fitted to estimate the simultaneous linear and nonlinear effects of temperature and density on CPUE. These models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 32 publications
6
51
3
1
Order By: Relevance
“…In roach from gill net catches (body lengths 137 -290 mm), the mean δ 15 N value was similar to small perch, i.e. approximately also observed in other lakes with these species (Brabrand & Borgstrøm 2000;van Dijk et al 2002;Linløkken & Haugen 2006). Burbot and Arctic charr, on the other hand, often staying in deeper water with lower temperatures (Hofmann & Fischer 2002;Klemetsen et al 2003), may have a lower catchability by gillnetting, and thereby a lower CPUE due to low temperatures (Borgstrøm 2000).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In roach from gill net catches (body lengths 137 -290 mm), the mean δ 15 N value was similar to small perch, i.e. approximately also observed in other lakes with these species (Brabrand & Borgstrøm 2000;van Dijk et al 2002;Linløkken & Haugen 2006). Burbot and Arctic charr, on the other hand, often staying in deeper water with lower temperatures (Hofmann & Fischer 2002;Klemetsen et al 2003), may have a lower catchability by gillnetting, and thereby a lower CPUE due to low temperatures (Borgstrøm 2000).…”
Section: Discussionsupporting
confidence: 75%
“…Apparently, the population density of Arctic charr in Lake Skasen is very low, but still catch data from one particular spawning site indicate that the mean body weight of spawners have decreased from approximately 218 g in 1992 -1996 to 91 g in 2006-2007, probably demonstrating that the population is squeezed due to interactions with other species. With the confined use of the profundal habitat of Arctic charr in Lake Skasen, intraspecific interactions may be important for the population dynamics, as observed in Lake Lønavatn, Western Norway (Jonsson & Østli 1979).…”
Section: Discussionmentioning
confidence: 97%
“…Other comparable studies [15,20] did not report any symptoms of prominent changes in species proportions when comparing data for 1*12 h vs. 3*4 h treatments and overnight vs. 1 h treatments, respectively. Contrary to our findings, even decreasing catchability with increasing density particularly for perch and to a lesser extent with roach has been found [9]. These species-specific differences definitely require further study.…”
Section: Discussioncontrasting
confidence: 55%
“…Unfortunately, this assumption typically does not hold for passive gill nets. Several studies [5][6][7][8][9][10] have reported a negative relationship between gill net catchability and abundance, and consequently CPUE may even appear asymptotically related to abundance.…”
Section: Introductionmentioning
confidence: 99%
“…The gillnet CPUE was higher at night probably due to higher activity of fish. Activity as a factor in increasing gill net catches has already been well described (Hamley 1975;Rudstam et al 1984;Linløkken and Haugen 2006). In addition, the gill-net is less visible in the dark, thus reducing fish avoidance and increasing catches.…”
Section: Discussionmentioning
confidence: 84%